Socio-Legal Approach in Land Acquisition Implementation for Public Interests: A Case Study of The Construction of A Connecting Bridge Batulicin – Kotabaru - Ismar Hamid; Erlina Erlina; Rachmat Hidayat; Rahmat Nur; Yusril Yusril; Muhammad Rifani; Muhammad Daffa Pratama (Fakultas Keguruan dan Ilmu Pendidikan, ULM, 2025)
This study examines the socio-legal approach to land acquisition for public purposes, focusing on the construction of the Batulicin-Kotabaru Bridge. Land acquisition is often a crucial point in infrastructure development, where legal norms interact with the social realities of the community. This qualitative study uses a socio-legal approach to analyze how the legal framework (Law No. 2 of 2012) is implemented in the field and how social dynamics—such as community perceptions, compensation issues, and deliberation processes—influence the project's success. Primary data was obtained through in-depth interviews with government officials, affected communities, and academics, while secondary data was collected from official documents and related literature. The results show that a socio-legal approach that integrates strong legal aspects with a deep understanding of the community's social conditions is highly effective in minimizing disputes. Active community involvement from the early stages, a transparent deliberation process (FGD), and the determination of fair and appropriate compensation values are key to success. This study recommends strengthening mediation mechanisms and proactive communication to ensure community rights are fulfilled, thereby enabling the achievement of development goals without causing social conflict.